Accuracy of Electrocardiography Criteria for Left Ventricular Hypertrophy in Hypertensive Patients at Shahid Gangalal National Heart Centre - Kharel, Sushant; Kadel, Arun; Acharya, Anjana; Neupane, Keshab Raj; Kunwar, Nikosh; KC, Sanjay Singh; Singh, Satish Kumar; Prajapati, Dipanker; Adhikari, Chandra Mani; Rajbhandari, Sujeeb; Rajbhandari, Rajib; Koirala, Umesh; et al. (Nepalese Heart Journal, 2024)
Background: Hypertension is the leading cause of cardiovascular disease and premature death worldwide. Left ventricular hypertrophy (LVH), a measure of hypertensive target organ damage in the heart is associated with increased morbidity, mortality and development of arrhythmias. This study was designed to identify the more accurate ECG criteria for identifying LVH taking LVH by echocardiography as reference.Methods: A cross sectional study was conducted at Shahid Gangalal National Heart Centre. A total of 252 patients were included. A 12-lead ECG and Echocardiography were done. Analysis done by SPSS 25. Stata-14 software was used for ROC (Receiver operating characteristics) comparison and P